2017
DOI: 10.1155/2017/3470320
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of 18β‐Glycyrrhetinic Acid against Triptolide‐Induced Hepatotoxicity in Rats

Abstract: Triptolide (TP) is the major active component of Tripterygium wilfordii Hook F (TWHF) and possesses multiple pharmacological effects. However, hepatotoxicity of TP which is one of the toxic properties slows its progression in clinical application. 18β-Glycyrrhetinic acid (GA) is the main bioactive ingredient of Licorice (Glycyrrhiza glabra L.), a herbal medicine famous for its detoxification. This study aims to investigate whether GA possesses protective effect against TP-induced hepatotoxicity in rats. TP int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Unfortunately, their application has been increasingly restricted due to their potential adverse effects and acute toxicity, particularly hepatic toxicity. To date, various studies have been performed with the aim of identifying strategies to reduce the side effects of these agents ( 24 26 ). However, counteractive therapeutic approaches against TP-induced hepatotoxicity are yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, their application has been increasingly restricted due to their potential adverse effects and acute toxicity, particularly hepatic toxicity. To date, various studies have been performed with the aim of identifying strategies to reduce the side effects of these agents ( 24 26 ). However, counteractive therapeutic approaches against TP-induced hepatotoxicity are yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the adverse events in the TwHF group were much lower than those in the glucocorticoid group (13 vs 19), and most adverse events in TwHF were mild and controllable. Other adverse reactions regarding TwHF, which have been reported in the literature were not noticed in our study, such as skin rashes, pigmentation, and genital dysfunction 14 . In this study, because the average age of patients was 78 years of age, this dose of more than 60 mg/day was not used on our patients.…”
Section: Discussionmentioning
confidence: 63%
“…These findings suggest that GA may serve as a novel chemotherapeutic potential for treating pituitary adenoma and deserves further clinical research. Previous studies demonstrated the protection of low-dose GA (50 mg/kg) against TP-induced hepatotoxicity in rats, which may mediate via anti-inflammation, antioxidation, and antiapoptosis (Yang et al, 2017[ 30 ]). In addition, the protective effect is dose-related, which is only mediated by low-dose GA (50 mg/kg), but not high-dose GA (100 mg/kg) (Yang et al, 2017[ 30 ]).…”
Section: Discussionmentioning
confidence: 99%